2017
DOI: 10.21014/acta_imeko.v6i3.457
|View full text |Cite
|
Sign up to set email alerts
|

Application of Gas Chromatography coupled with Mass Spectroscopy (GC/MS) to the analysis of archeological ceramic amphorae belonging to the Carthaginian fleet that was defeated in the Egadi battle (241 B.C.)

Abstract: <p class="Abstract"><span lang="EN-US">The aim of this preliminary work was to identify characteristic compounds in 7 underwater marine ceramic amphorae sherds dating from the period of the battle of the Egadi Islands that decided the end of the First Punic War (241 B.C.) by Gas Chromatography coupled with Mass Spectroscopy (GC/MS).</span></p>

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
13
0

Year Published

2020
2020
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(14 citation statements)
references
References 5 publications
1
13
0
Order By: Relevance
“…Sarcophagus #2 results show the presence of Pinaceae resin in the preparatory layer, while a mixture of beeswax and the Pinaceae resin was observed in the brown paint layer. Chemical analyses of Late Roman-Egyptian adhesives showed similar results [51]. The use of these adhesives has been documented in Ancient Egyptian times, both separately and as mixtures.…”
Section: Binderssupporting
confidence: 58%
See 1 more Smart Citation
“…Sarcophagus #2 results show the presence of Pinaceae resin in the preparatory layer, while a mixture of beeswax and the Pinaceae resin was observed in the brown paint layer. Chemical analyses of Late Roman-Egyptian adhesives showed similar results [51]. The use of these adhesives has been documented in Ancient Egyptian times, both separately and as mixtures.…”
Section: Binderssupporting
confidence: 58%
“…To allow a better identification of the organic markers in the binders, Pyrolysis Gas Chromatography Mass Spectroscopy (Py-GC/MS) analyses were performed as a complementary analytical technique [48,[50][51][52]. For this study, an innovative methodology to Py-GC/MS data interpretation using expert knowledge integrated into a Microsoft Excel workbook was selected-ESCAPE: Expert System for Characterization using AMDIS Plus Excel.…”
Section: Bindersmentioning
confidence: 99%
“…This technique allows for the accurate quantification of analytes. For instance, the oil content was analyzed in ancient amphorae found in the Late Bronze Age shipwreck of Uluburun [ 26 ] and the site of Amarna (Egypt) [ 44 ], or shipwrecks dating from the First Punic War [ 45 ]. In addition, the profiling of the adsorbed oil gradient within the clay fabric of potsherds has been investigated [ 44 ].…”
Section: Introductionmentioning
confidence: 99%
“…Beeswax can be applied post-firing to make the vessel water resistant because of its hydrophobic nature [ 1 ]. This has been frequently suggested in ORA studies that identified beeswax [ 9 , 21 , 30 , 44 , 84 ]. A beeswax sealant would benefit vessels meant to store liquids, and correspondingly, beeswax biomarkers were identified in vessel forms related to storage and liquids—jars in this study and amphorae, juglets, flasks and chalices in previous studies [ 24 , 44 , 84 ].…”
Section: Discussionmentioning
confidence: 90%
“…This has been frequently suggested in ORA studies that identified beeswax [ 9 , 21 , 30 , 44 , 84 ]. A beeswax sealant would benefit vessels meant to store liquids, and correspondingly, beeswax biomarkers were identified in vessel forms related to storage and liquids—jars in this study and amphorae, juglets, flasks and chalices in previous studies [ 24 , 44 , 84 ]. Cooking vessels would likely not receive a beeswax sealant because beeswax melts at 62–65°C [ 15 ], so the sealant would need to be frequently reapplied, and the flavour and texture of the sealant could be undesirably incorporated into the cooked food.…”
Section: Discussionmentioning
confidence: 90%